Germination of Jamblang (Syzygium Cumini) Seeds on Three Treatments of Pre-Germination And Sowing Media - Aris Sudomo; Dila Swestiani (Balai Litbang Teknologi Agroforestry, Ciamis, 2018)
Generative propagation was needed as one of efforts in developing jamblang as a medicinal plant. This study aims to improve the percentage and germination rate of jamblang seeds through pre-germination and sowing media treatments. The combination of treatments were (1) soil (T) x water (AB), (2) soil (T) x coconut water (AK), (3) soil (T) x control (without soaking treatment) (K), (4) sand (P) x water (AB), (5) sand (P) x coconut water (AK), (6) sand (P) x control (K), (7) mixed soil-sand (TP) x water (AB), (8) mixed soil-sand (TP) x water (AB), and (9) mixed soil-sand (TP) x control (K). The results revealed that the treatments of sowing seeds with mixed media soil + sand and pre-germination treatments by soaking the seeds for 12 hours in coconut water gave the highest percentage (70%) and germination rate (4.96%). Percentage of germination more than 50% only can be reached by the seeds that sowed on mixed soil + sand with pre-germination treatments soaked in coconut water for 12 hours and in water for 12 hours. The improvement in the percentage and germination rate of jamblang were achieved by using mixed sowing media soil + sand and pre-germination treatment by soaking in coconut water.